2012
DOI: 10.1136/injuryprev-2011-040306
|View full text |Cite
|
Sign up to set email alerts
|

Differences in incidence of injury between rural and urban children in Canada and the USA: a systematic review

Abstract: These findings indicate the need of developing geographic area-specific injury-prevention strategies. Future research is required to investigate rural-urban disparity for less-studied injuries and related health outcomes (eg, disability). Systematic review registration number CRD42011001244 (PROSPERO 2011).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
48
2
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 68 publications
(200 reference statements)
8
48
2
3
Order By: Relevance
“…The underlying mechanism may be a higher exposure to a wider range of hazards in the living environment, and lack of means of protection 64. A large proportion of indigenous people live in remote areas, and remoteness, in turn, has been linked with higher rates of injuries 65 66. This has been attributed to greater exposure to risk factors, in particular, for transport-related injuries, and reduced access to and lower quality of healthcare in remote areas 54.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The underlying mechanism may be a higher exposure to a wider range of hazards in the living environment, and lack of means of protection 64. A large proportion of indigenous people live in remote areas, and remoteness, in turn, has been linked with higher rates of injuries 65 66. This has been attributed to greater exposure to risk factors, in particular, for transport-related injuries, and reduced access to and lower quality of healthcare in remote areas 54.…”
Section: Discussionmentioning
confidence: 99%
“…This has been attributed to greater exposure to risk factors, in particular, for transport-related injuries, and reduced access to and lower quality of healthcare in remote areas 54. Higher rates of transport injuries have been explained by longer travelling distances, poorer quality roads, driver fatigue, failure to use seatbelts, alcohol and drug use, overcrowding of cars, unsafe cars and travelling at higher speeds 11 15 65 6769. Road safety measures might also be less vigorously enforced in remote areas,4 and the autonomous legal status of reservations might lead to different road safety laws and less stringent law enforcement 2 40…”
Section: Discussionmentioning
confidence: 99%
“…After excluding bathtub drowning deaths to analyze drownings possibly related to swimming and/or water safety skills, men and women from rural areas had a significantly higher risk of drowning compared with their non-rural counterparts. Previous studies have found rural residency to be associated with an increased risk of drowning, but the majority of these studies were restricted to pediatric drowning deaths (Fang et al, 2007;Hammig & Weatherly, 2003;Kim, Ozegovic, & Voaklander, 2012;Ma et al, 2010;Rahman et al, 2006;Svenson et al, 1996;World Health Organization, 2012). Our study is unique in that we included all ages of drowning victims.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that increased access to open water compounded with decreased access to swimming lessons in rural areas may explain the difference in drowning rates (Fang et al, 2007). A systematic review from North America of drowning deaths and other preventable injuries suggested that socioeconomic status and access to medical care might also explain the higher rates of injury in rural areas (Kim et al, 2012). Further, aboriginal people are at increased risk of drowning and aboriginal groups are more likely to live in rural Ontario (Frohlich, Ross, & Richmond, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…31 The NOS Cohort uses 8 criteria to evaluate selection bias, cohort comparability, and outcome assessment and has been used in another injury-related review. 32 The NOS Case Control uses 8 criteria to evaluate selection bias, comparability of groups, and exposure ascertainment. We modified the NOS Case Control to better serve the needs of this review (Supplemental Table 5).…”
mentioning
confidence: 99%